Consequences of the crisis of Corona on the sectors of the world economy - reading in the economic indicators - بن زكورة لعوينة (Finance and Business Economies Review, 2020)
This study aims to highlight on the corona epidemic ramifications on the international economy, from reading the most important international economic indicators and that to identify the extent of the epidemic’s contribution to causing a global economic crisis that may be the most difficult in this century. The international economic has experienced a decline in its various fields due to precautionary measures taken by the governments of the countries represented in quarantine, the resulting paralysis in various economic sectors such as transportations, financial markets, economic institutions, unemployment, tourism and other indicators.